THE ROLE OF COMMUNICATIVE LANGUAGE TEACHING IN DEVELOPING ENGLISH SPEAKING SKILLS AMONG TECHNICAL COLLEGE STUDENTS - Ilhomjonova Gulhayo, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article discusses the importance of Communicative Language Teaching (CLT) in developing English speaking skills among technical college students. Modern vocational education requires learners not only to possess professional knowledge but also to communicate effectively in English. The study examines the principles of CLT, its advantages in language classrooms, and its impact on students’ communicative competence. The article also presents practical recommendations for English teachers working in technical colleges.